2018
DOI: 10.3390/ijfs6030063
|View full text |Cite
|
Sign up to set email alerts
|

Bank Interest Margin, Multiple Shadow Banking Activities, and Capital Regulation

Abstract: Abstract:In this paper, we develop a contingent claim model to evaluate a bank's equity and liabilities that integrates the premature default risk conditions with loan rate-setting behavioral mode and multiple shadow banking activities under capital regulation. The barrier options theory of corporate security valuation is applied to the contingent claims of a bank. The barrier reports that default can occur at any time before the maturity date. We focus on a type of earning-asset portfolio, consisting of balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…A wealth of literature has investigated the performance of financial institutions. In the past decade, research has examined the determinants of financial institutions' performance, analyzing how firms address corporate governance issues (Aebi et al, 2012;Peni and Vähämaa, 2012;Zheng and Das, 2018), master the diversification of their business activities (Berger et al, 2010;Brahmana et al, 2018;Chen et al, 2018;Kim et al, 2020), deal with external regulation (Naceur and Omran, 2011;Psillaki and Mamatzakis, 2017), react to monetary policies (Mamatzakis and Bermpei, 2016;Gambacorta and Shin, 2018), deal with the legal and institutional framework (Kalyvas and Mamatzakis, 2017;Bitar and Tarazi, 2019;El Ghoul et al, 2021), generate intellectual capital (Talavera et al, 2018;Nawaz, 2019;Adesina, 2021), and engage in shadow banking activities (Tan, 2017;Lin et al, 2018). Given the all-embracing and massive development of the fintech sector in the past decade, it seems worthwhile also to investigate how fintech start-up formations affect financial institutions' performance.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…A wealth of literature has investigated the performance of financial institutions. In the past decade, research has examined the determinants of financial institutions' performance, analyzing how firms address corporate governance issues (Aebi et al, 2012;Peni and Vähämaa, 2012;Zheng and Das, 2018), master the diversification of their business activities (Berger et al, 2010;Brahmana et al, 2018;Chen et al, 2018;Kim et al, 2020), deal with external regulation (Naceur and Omran, 2011;Psillaki and Mamatzakis, 2017), react to monetary policies (Mamatzakis and Bermpei, 2016;Gambacorta and Shin, 2018), deal with the legal and institutional framework (Kalyvas and Mamatzakis, 2017;Bitar and Tarazi, 2019;El Ghoul et al, 2021), generate intellectual capital (Talavera et al, 2018;Nawaz, 2019;Adesina, 2021), and engage in shadow banking activities (Tan, 2017;Lin et al, 2018). Given the all-embracing and massive development of the fintech sector in the past decade, it seems worthwhile also to investigate how fintech start-up formations affect financial institutions' performance.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…Tan (2017) notes that traditional banks conduct shadow banking activities to boost profitability. Lin et al (2018) and Fang et al (2019) show that the involvement of conventional banks in shadow banking activities leads to superior performance. In addition to its impact on profitability, shadow banking activities also affect traditional banks’ cost efficiency.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Their findings showed that the NFNE futures exhibit superior effectiveness as an instrument for hedging stock sector exposures, compared with the TAIEX and Taiwan 50 futures. The ninth paper entitled "Bank Interest Margin, Multiple Shadow Banking Activities, and Capital Regulation by Lin et al (2018) investigates a contingent claim model to evaluate a bank's equity and liabilities that integrates the premature default risk conditions with loan rate-setting behavioral mode and multiple shadow banking activities under capital regulation. The authors focused on a type of earning asset portfolio, consisting of balance sheet banking activities of loans and liquid assets and shadow banking activities of wealth management products (WMPs) and entrusted loans (ELs).…”
Section: Papersmentioning
confidence: 99%